IMPLEMENTASI PROGRAM PEMBANGUNAN PERUMAHAN DAN LINGKUNGAN DESA TERPADU (P2LDT) - Nur Islami, Mona Erythrea (Sekolah Tinggi Pariwisata AMPTA, 2008)
A house is one of people’s primary needs. However, people in rural area sometimes do not realize the importance of a proper house to live in. The government through integral settlement and rural environment developing program has been trying to change the perspective of rural people. Success of this program depends on how the people make it so that this program is always on progress and continuity takes place.